2011
DOI: 10.2197/ipsjjip.19.212
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Anxieties while Using the Internet to Study about “Anshin”

Abstract: "Anshin" is an emotion in Japanese that is difficult to translate because it is vague, varies from person to person, and is subjective. It means something like "a feeling of contentment". The demand for Internet use with "Anshin" is high. We believe that the emotion and the demand could be universal. To study "Anshin," we conducted group interviews as our first step. We obtained 95/157 cases of "Anshin"/anxiety from 28 people. From the results, we found that studying anxiety is valuable. Anxiety is a kind of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It was caused from the inadequacy of infrastructure for net shopping. Regarding the net use, it was also revealed that the contents and levels of consumers' anxiety of ten countries were different (Chiba et al, 2013;Yamamoto et al, 2011;Yamamoto et al, 2012).…”
Section: Cross-border Consumer Center Japanmentioning
confidence: 99%
“…It was caused from the inadequacy of infrastructure for net shopping. Regarding the net use, it was also revealed that the contents and levels of consumers' anxiety of ten countries were different (Chiba et al, 2013;Yamamoto et al, 2011;Yamamoto et al, 2012).…”
Section: Cross-border Consumer Center Japanmentioning
confidence: 99%
“…Similarly, in a survey conducted in New York, a major reason for refusing to participate in a huge repository of DNA and health records was personal privacy (Kerath et al, 2013). Of note, a recent survey comparing 10 different countries showed that the Japanese population, including both men and women, was most concerned about protecting personal information (Yamamoto et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Sekiya (2012) analyzed the purposes of Twitter use after the 2011 disaster. Kawai and Fujishiro (2013) analyzed how people used Twitter to obtain disaster-related information, and Yamamoto et al (2012) examined the influence of Twitter use on people's perception of "safety" and "anxiety" following the disaster.…”
Section: Social Media In Disaster Studiesmentioning
confidence: 99%